Targeting Hypoxia Inducible Factors-1α As a Novel Therapy in Fibrosis - Xiong, Anji; Liu, Yi (Frontiers in Pharmacology, 2017)
Fibrosis, characterized by increased extracellular matrix (ECM) deposition, and widespread vasculopathy, has the prominent trait of chronic hypoxia. Hypoxia inducible factors-1α (HIF-1α), a key transcriptional factor in response to this chronic hypoxia, is involved in fibrotic disease , such as Systemic sclerosis (SSc). The implicated function of HIF-1α in fibrosis include stimulation of excessive ECM, vascular remodeling, and futile angiogenesis with further exacerbation of chronic hypoxia and deteriorate pathofibrogenesis. This review will focus on the molecular biological behavior of HIF-1α in regulating progressive fibrosis. Better understanding of the role for HIF-1α-regulated pathways in fibrotic disease will accelerate development of novel therapeutic strategies that target HIF-1α. Such new therapeutic strategies may be particularly effective for treatment of the prototypic, multisystem fibrotic, autoimmune disease SSc.